2022
DOI: 10.1186/s40337-022-00658-y
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of associations between the ICD-11 personality disorder model and eating pathology

Abstract: Background Recently, the International Classification of Diseases 11th Revision (ICD-11) has introduced a paradigm shift in personality disorder conceptualization. The novel ICD-11 personality disorder model comprises a dimensional assessment of personality dysfunction and five maladaptive personality trait domains. Maladaptive personality plays a central role in eating pathology. Yet, relations between the ICD-11 personality disorder model and eating pathology are, to date, unclear. Thus, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Some facets of the DSM‐5 model, such as Distractibility and Impulsivity, which were expected to load strongly on the Disinhibition factor, loaded more strongly on the Negative Affectivity factor. Several studies have shown a relationship between the disinhibited features and both the BED and BSD (Hays & Roberts, 2008; Jen et al, 2013; Komasi et al, 2023; Shi et al, 2022; Sparding et al, 2017; Stricker et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some facets of the DSM‐5 model, such as Distractibility and Impulsivity, which were expected to load strongly on the Disinhibition factor, loaded more strongly on the Negative Affectivity factor. Several studies have shown a relationship between the disinhibited features and both the BED and BSD (Hays & Roberts, 2008; Jen et al, 2013; Komasi et al, 2023; Shi et al, 2022; Sparding et al, 2017; Stricker et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…So far, several studies tried to report the association between the DSM‐5 and the ICD‐11 domains and all personality disorders according to the used classifications by previous versions of the manuals (Al‐Dajani et al, 2016; Fang et al, 2021; Fossati et al, 2013; Fossati et al, 2016). However, the transdiagnostic personality domains proposed by both systems may apply not only to the assessment of personality pathology but to other mental disorders as well (Hong & Tan, 2021; Komasi et al, 2023; Sellbom et al, 2020; Stricker et al, 2022). For example, the antagonistic and disinhibited externalizing spectra of the Hierarchical Taxonomy of Psychopathology (HiTOP) cover several personality disorders and substance‐related disorders, whereas the internalizing spectrum (linked to Negative Affectivity) covers a wide range of mental disorders, including anxiety, sexual, eating, and affective disorders (Kotov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations